efectos de algunos insecticidas en dosis subletales sobre adultos de Aphidius ervi Haliday (Hymenoptera: Aphididae) - Araya, M.N.=700 1 Araya, J.E.; Guerrero, M.A.
(En, Es)
ilus., 40 ref.
Keywords: ACYRTHOSIPHOM PISUM; APHIDUS ERVI; DIMETOATO; PIRIMICARB; CONTROL QUIMICO; ESPAÑA; IMIDACLOPRID